2017
DOI: 10.1016/j.ajo.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

West Indies Glaucoma Laser Study (WIGLS): 1. 12-Month Efficacy of Selective Laser Trabeculoplasty in Afro-Caribbeans With Glaucoma

Abstract: Purpose To characterize the 12-month intraocular pressure (IOP)-lowering efficacy of selective laser trabeculoplasty (SLT) as sole therapy for primary open-angle glaucoma (POAG) in an Afro-Caribbean population. Design Stepped-wedge trial. Methods Subjects in St. Lucia and Dominica with established POAG were randomized to prompt washout of IOP-lowering medications followed by SLT, 3-month delay followed by washout and SLT, or 6-month delay followed by washout and SLT. Baseline IOP was obtained on two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 27 publications
3
21
2
Order By: Relevance
“…Realini et al 31 found total laser power not to be a significant predictor of 12month success, with a mean (SD) of 86.0 (21.1) mJ in the right eye and 87.7 (20.6) mJ in the left eye compared with a mean (SD) of 90.4 (23.5) mJ in our study. 8 In contrast, Lee et al 32 found that greater total SLT energy was associated with a greater IOP lowering but this study was limited by small sample size, short follow-up (1 month), and total energy powers that were considerably higher than used here (optimum total reported as 226.1 mJ). Habib et al 33 divided patients receiving 360 degree SLT treatment into those who received low (<85 mJ), medium (85e105 mJ), or high (>105 mJ) energy SLT.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Realini et al 31 found total laser power not to be a significant predictor of 12month success, with a mean (SD) of 86.0 (21.1) mJ in the right eye and 87.7 (20.6) mJ in the left eye compared with a mean (SD) of 90.4 (23.5) mJ in our study. 8 In contrast, Lee et al 32 found that greater total SLT energy was associated with a greater IOP lowering but this study was limited by small sample size, short follow-up (1 month), and total energy powers that were considerably higher than used here (optimum total reported as 226.1 mJ). Habib et al 33 divided patients receiving 360 degree SLT treatment into those who received low (<85 mJ), medium (85e105 mJ), or high (>105 mJ) energy SLT.…”
Section: Discussioncontrasting
confidence: 74%
“…A previous study found that the only significant predictor of IOP lowering at 12 months across all eyes was time, with the maximum IOP reduction seen at 3 months followed by a slow decline in effect subsequently. 31 Although we found successful eyes achieving drop-free disease-control after initial single SLT at 36 months had a lower IOP at 2 months compared with non-successful eyes (adjusted mean difference ¼ À1.9 mmHg; 95% CI, À1.4 to À2.3 mmHg), there may not be enough specificity in this observation (because of the SD of IOP measurements) to be helpful in the individual case.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The WIGLS protocol has been described in detail elsewhere 25 and was registered at clinicaltrials.gov prior to the enrollment of any subjects (NCT02375009). Briefly, a convenience sample of subjects with primary open-angle glaucoma (based on ISGEO criteria 26 ) was drawn from eyecare practices in St. Lucia and Dominica.…”
Section: Methodsmentioning
confidence: 99%
“…Primary outcomes at 12 months have been previously reported. 25 Efforts are now underway to globalize availability to SLT for people of African descent living in low-resource settings. In this report, we present the results of a planned analysis to identify factors associated with IOP reduction during the first 12 months following initial SLT treatment in people of African descent with POAG.…”
Section: Introductionmentioning
confidence: 99%